Analisis Strategi Pemasaran Melalui Pemasaran Online Untuk Meningkatkan Minat Beli Konsumen di Soft Coffee Masamba - Muh Afdal Al Fatha; Suhardi M. Anwar; Andi Rizkiyah Hasbi (SEIKO : Journal of Management & Business, 2023)
In marketing it is known that after consumer purchasing decisions, a process occurs called satisfied and dissatisfied consumers, namely the relationship between expectations and product or service achievement. If the product or service does not meet expectations, consumers will no longer buy it. On the other hand, when a product or service exceeds consumer expectations, consumers feel satisfied and are likely to make repeat purchases Internet marketing in the same language is a strategy to introduce consumers/audience to a company's or business's brand, product or service. Network marketing, also known as internet marketing and some call it online advertising. In this case the media used is the internet. The easiest thing to remember is how to always update a product or service to make it easier to find online and purchase intention is used to describe the process of creating confidence. ). Consumer attitudes and cognitive information behavior through a combination of attributes, benefits and objects (evaluation of information), while attitudes refer to feelings or affective responses. Attitudes act as cues that influence the environment Keywords: online marketing, buying interest